Displacement in a fragile Iraq - Ali, A (Refugee Studies Centre, University of Oxford, 2013)
The post-Saddam Iraqi state enjoys only limited support from the population, excludes significant sections of its people from power, suppresses the opposition and does not protect citizens from arbitrary arrests, and corruption is rampant. There is a direct relationship between these failures and displacement in Iraq.